3x+7=-1+9x
i.e.
9x-3x=7+1
therefore 6x=8
x= 8/6= 4/3
2007-06-12 17:54:08
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
x=1 1/3
2007-06-13 00:52:24
·
answer #2
·
answered by TG 7
·
0⤊
0⤋
3x - 9x = - 1 - 7
-6x = -8
x = 8/6
x = 4/3 or 1 1/3
2007-06-13 01:00:19
·
answer #3
·
answered by kayedimanche 2
·
0⤊
0⤋
4/3=x
2007-06-13 00:52:18
·
answer #4
·
answered by Belldoll 4
·
0⤊
0⤋
3x + 7 = -1 + 9x
7+1 = 6x
8 = 6x
x = 4/3 = 1 1/3
2007-06-13 00:55:07
·
answer #5
·
answered by d_xtreme93 1
·
0⤊
0⤋
Add 1 to each side - 3x + 8 = 9x
Subtract 3x from each side - 8 = 6x
Divide each side by 6
x= 4/3
2007-06-13 00:56:16
·
answer #6
·
answered by MC 3
·
0⤊
0⤋
3x+7=-1+9x
3x+7-7=-1+9x-7
3x=-8+9x
3x+8=-8+9x+8
3x-3x+8=9x-3x
8=6x
8/6=6x/6
8/6 or 4/3 or 1 1/3or 1.3333=x
2007-06-13 01:00:47
·
answer #7
·
answered by guy_from_Dallas 4
·
0⤊
0⤋
bring terms of x on one side & other terms to other side
7+1=9x-3x
8=6x
8/6=x
x=8/6
x=4/3 or 1 1/3
2007-06-13 00:54:33
·
answer #8
·
answered by Jain 4
·
0⤊
0⤋
3x-3x+7=-1+9x-3x
7=-1+6x
7+1=-1+1+6x
8=6x
8/6=6x/6
8/6=x = 4/3=x
2007-06-13 00:55:09
·
answer #9
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
3x+9x=-1-7
12x=-8
x=-8/12
x=-2/3
ANS: -2/3
2007-06-13 01:21:01
·
answer #10
·
answered by JMdipto 3
·
0⤊
1⤋